Prosthetic Exo-leg: A multifunctional robotic leg-suit to support patient with transfemoral amputation - Enam, Fahin Uddin; Nipa, Fahmida Yasmin; Ahmed Abir, Md. Tahsin; Mahin, Musa Ahammed (Brac University, 2024)
This final year design project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2022.